1994
DOI: 10.1002/ajh.2830450205
|View full text |Cite
|
Sign up to set email alerts
|

Varying populations of CD59‐negative, partly positive, and normally positive blood cells in different cell lineages in peripheral blood of paroxysmal nocturnal hemoglobinuria patients

Abstract: CD59-antigen expression on the surface membranes of erythrocytes, granulocytes, monocytes, lymphocytes, and platelets was determined by flow cytometry in 34 healthy controls and 17 patients with paroxysmal nocturnal hemoglobinuria (PNH). In all PNH patients, CD59-negative erythrocytes accounted for > 10% of the total erythrocyte population. Two erythrocyte populations (CD59-negative and normally positive or CD59-negative and partly positive), three populations (CD59-negative, partly positive, and normally posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Measuring populations of platelets deficient in GPI-linked proteins by flow cytometry is a sensitive method of studying the relationship between these proteins and thrombosis. Published works using flow cytometry show such variability of percentage CD59 expression as to make discrimination between PNH and normal platelets impossible (Fujioka & Yamada, 1994). Vu et al (1996) reported they could not discriminate between PNH II and PNH III platelets due to low mean fluorescence intensity (MFI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measuring populations of platelets deficient in GPI-linked proteins by flow cytometry is a sensitive method of studying the relationship between these proteins and thrombosis. Published works using flow cytometry show such variability of percentage CD59 expression as to make discrimination between PNH and normal platelets impossible (Fujioka & Yamada, 1994). Vu et al (1996) reported they could not discriminate between PNH II and PNH III platelets due to low mean fluorescence intensity (MFI).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement of GPI-linked protein-deficient populations of platelets would therefore be important for studying the relationship with thrombosis. Previous reports of CD59 expression on platelets have been unable to discriminate between PNH and normal platelets (Fujioka & Yamada, 1994;Vu et al, 1996). In the present study, platelet CD55 and CD59 patterns of expression were analysed in patients with PNH and AA, and normal controls.…”
mentioning
confidence: 99%
“…Absence of red cell surfaces of complement regulatory proteins such as CDS9 and decay-accelerating factor (DAF) is responsible for the hypersensitivity to complement of the red cells [18,19]. DAF, CDS9 and some other membrane proteins are inserted to the red cell surface via a glycosylphosphatidylinositol (GPI) moiety.…”
Section: Pnhmentioning
confidence: 99%
“…Red cells and granulocytes display complete (type III) or partial (type II) deficiency of GPI-linked proteins [30]. Type III red cells are most sensitive to the effects of complement.…”
Section: Pathogenesismentioning
confidence: 99%